2021
DOI: 10.31234/osf.io/h3957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Situational factors influencing social anxiety in treatment-seeking adults who stutter: An exploratory factor analysis

Abstract: Purpose: Adults who stutter (AWS) often show high levels of social anxiety. Stuttering is a speech disorder, making the latent factors influencing social anxiety potentially different from those in individuals with a social anxiety disorder (SAD) or general populations. This study aims to examine the situational factors influencing social anxiety in AWS.Methods: We analyzed data of 351 AWS using the fear/anxiety scale in the Japanese self-report version of the Liebowitz Social Anxiety Scale (LSAS). We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…VRET targeting general social fears will be more appropriate for the majority of PWS. Findings from a recent preprint suggest that, besides speaking on the phone, situational factors influencing social anxiety were largely similar in PWS and fluent speakers, including those with SAD (75). Findings from another preprint also showed that general speech-related fears are common across PWS (76).…”
Section: Public Speaking Vs General Social Anxietymentioning
confidence: 97%
See 1 more Smart Citation
“…VRET targeting general social fears will be more appropriate for the majority of PWS. Findings from a recent preprint suggest that, besides speaking on the phone, situational factors influencing social anxiety were largely similar in PWS and fluent speakers, including those with SAD (75). Findings from another preprint also showed that general speech-related fears are common across PWS (76).…”
Section: Public Speaking Vs General Social Anxietymentioning
confidence: 97%
“…However, there are some situational factors that should be considered when designing VRET protocols. Findings from both of the above preprints suggest that fear of speaking on the telephone is particularly elevated amongst PWS and may constitute a distinguishable sub-type of social anxiety amongst PWS (75,76). A telephone-only treatment may therefore be appropriate for some PWS.…”
Section: Public Speaking Vs General Social Anxietymentioning
confidence: 98%
“…Participants were recruited through online adverts on the British Stammering Association's website (Stamma.org), and through local stuttering groups across the United Kingdom. Inclusion criteria were (1) Person who stutters, (2) English-speaking, (3) United Kingdom resident, (4) age over 18, (5) in possession of a smartphone (iPhone/Android) and headphones/earphones, (6) no previous participation in the feasibility trial or focus groups for same treatment, (7) no current experience of psychosis/ schizophrenia/epilepsy/dementia/amnesia/bipolar disorder/ intellectual disability/autism spectrum disorder, (8) no current use of tranquilizers or change in dosage of antidepressants in the past 6 weeks, (9) no current suicidal ideation, (10) no alcohol/substance dependence, (11) no severe cognitive impairment, (12) no treatment for social anxiety within the last year, (13) not participating in any other psychotherapeutic treatments during the study, and (14) no experience of severe cyber/motion-sickness. All participants who completed the pre-and post-treatment assessments (or equivalent for waitlist) received a £10 Amazon evoucher.…”
Section: Participantsmentioning
confidence: 99%
“…As such, anxiety is embedded in speech and revolves around fears of others’ negative reactions to stuttering ( 9 ). Speaking on the telephone is one of the most commonly reported fears, to the extent that it may constitute its own sub-type of social anxiety among PWS ( 10 , 11 ). Avoidance of certain words and situations is also a core theme in the lived experience of stuttering ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, anxiety is embedded in speech and revolves around fears of others' negative reactions to stuttering (9). Speaking on the telephone is one of the most commonly reported fears, to the extent that it may constitute its own sub-type of social anxiety among PWS (10,11). Avoidance of certain words and situations is also a core theme in the lived experience of stuttering (12).…”
Section: Introductionmentioning
confidence: 99%